Transparent Conductors: Structural Optimization of Oxide/Metal/Oxide Transparent Conductors for High‐Performance Low‐Emissivity Heaters (Adv. Mater. Interfaces 24/2018). Issue 24 (20th December 2018) - Li, Peng; Li, Huapeng; Ma, Jiangang; Zhou, Yu; Zhang, Wei; Cong, Lujia; Xu, Haiyang; Liu, Yichun
Abstract : In article number1801287, Peng Li, Jiangang Ma, Yichun Liu, and coworkers proposed a structural optimization method that enables the fabrication of oxide/metal/oxide films with high visible light transmittance, infrared reflectance, and conductivity. The films have potential for use on windows that maintain indoor warmth in winter and cool in summer.